Central Hypogonadotropic Hypogonadism: Genetic Complexity of a Complex Disease - Marco Marino; Valeria Moriondo; Eleonora Vighi; Elisa Pignatti; Manuela Simoni (International Journal of Endocrinology)
Central hypogonadotropic hypogonadism (CHH) is an emerging pathological condition frequently associated with overweight, metabolic syndrome, diabetes, and midline defects. The genetic mechanisms involve mutations in at least twenty-four genes regulating GnRH neuronal migration, secretion, and activity. So far, the mechanisms underlying CHH, both in prepubertal and in adulthood onset forms, remain unknown in most of the cases. Indeed, all detected gene variants may explain a small proportion of the affected patients (43%), indicating that other genes or epigenetic mechanisms are involved in the onset of CHH. The aim of this review is to summarize the current knowledge on genetic background of CHH, organizing the large amount of data present in the literature in a clear and concise manner, to produce a useful guide available for researchers and clinicians.